Study of the antineoplastic action of Tabebuia avellanedae in carcinogenesis induced by azoxymethane in mice - Higa,Roberta Alves (2011)
PURPOSE: To study the antitumor action of Tabebuia avellanedae in experimentally induced colon carcinogenesis by azoxymethane in mice. METHODS: Fifty (n=50) mice were divided into five groups: in group I azoxymethane (AOM) was administered, in Group II - β-lapachone, in group III - vehicle (diluent) and in group IV - vehicle + AOM and finally in group V - β-lapachone + AOM. RESULTS: It was observed the presence of aberrant crypt foci in all animals of groups I and IV, 50% in group II and 90% in group V. CONCLUSION: The β-lapachone extracted from the Tabebuia avellanedae showed no protective effect of lesions induced by azoxymethane in colon of mice.